Calling behavior and ovarian development of Spodoptera frugiperda populations resistant to Bt toxins - Sousa, Fernanda Freitas (2016)
Transgenic crops have been adopted for pest control since 1996 and among the benefits of using this technology are the effective control of target pests and low risk to non-target organisms. However, the evolution of resistance is a major threat to the long-term efficacy of such technology. Insect resistant can express physiological cost, which helps reverse the occurrence of resistance to Bt crops when refuge is present. Spodoptera frugiperda is the most destructive pest of maize in tropical regions of the Americas and have been documented cases of resistance to Bt corn events that produce Cry1F toxin. It has already been observed fitness cost associated with resistance Cry1Fa in life cycle characteristics, but was not observed cost in reproductive parameters. Moreover, it was observed cost associated with resistance to Bt maize stacked event in the life cycle characteristics and fertility parameters. However, behavioral features (e.g., calling) have been little studied as possible characteristics of cost. This work was carried out to study the calling behavior and compare the ovarian development of Spodoptera frugiperda female susceptible and resistant to GM maize expressing Cry1Fa and other event that expresses toxins Cry2Ab2 and Cry1A.105. Resistant to first-generation event expressing Cry1Fa toxin females started calling earlier, spend more time calling and generally have higher number and most enduring calling bouts than susceptible female during scotophase. There was no difference between the of the basal oocytes width between resistant and susceptible females, but resistant females showed more mature eggs than susceptible at the same age after emergence, besides presenting mature eggs one day before. Resistant females to second-generation Bt event expressing Cry2Ab2 and Cry1A.105 toxins showed no difference in the mean onset time of calling. Nevertheless, the resistant females generally spend more time calling in addition to present a larger number of call bouts during the scotophase. At 12 hours after emergence, resistant females have larger basal oocytes width compared to susceptible, and this value becomes equal at 24 hours after emergence. In early adulthood, the resistant and susceptible females did not differ in number of mature eggs, but after 72 hours this number is higher in susceptible females. Therefore, although there are advantages in the calling behavior, there is a cost in the number of mature eggs associated with Bt stacked expressing Cry2Ab2 and Cry1A.105 toxins resistance in the population of S. frugiperda tested. However, no cost Cry1Fa resistance, and resistant females showed a higher performance than susceptible.